Basic lexical and grammatical transformations in translation of German print advertising - A N Mamedov (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2014)
The article presents basic lexical and grammatical transformations, which contribute to preserving the semantic and syntactic structure of a German advertising text and reproducing the image of the advertised product. This shows that the translation has the same communicative effect as that achieved by the source text.